Methamphetamine- and 3,4-Methylenedioxymethamphetamine-Induced Behavioral Changes in Histamine H3-Receptor Knockout Mice - Tomohiro Okuda; Dongying Zhang; He Shao; Nobuyuki Okamura; Naoko Takino; Tatsunori Iwamura; Eiko Sakurai; Takeo Yoshikawa; Kazuhiko Yanai (Elsevier, 2009)
Histamine H3 receptors inhibit the release of not only histamine itself, but also other neurotransmitters including dopamine. Previous papers have reported that histaminergic neurons inhibit psychostimulant-induced behavioral changes. To examine whether deficiency in histamine H3 receptors influences psychostimulant-induced behavioral sensitization and reward, we examined locomotor activity, conditioned place preference (CPP), and c-Fos expression in histamine H3 receptor-gene knockout mice (H3KO) and their wild-type (WT) counterparts before and after treatment with methamphetamine (METH) and 3,4-methylenedioxymethamphetamine (MDMA). The increase in locomotion induced by treatment with METH or MDMA was lower in histamine H3KO mice than in WT mice, while the locomotor sensitization was developed by METH or MDMA in both strains. However, no significant difference in METH- and MDMA-induced preference scores of CPP between histamine H3KO mice and WT mice was observed. Following treatment with METH, the number of c-Fos-positive neurons in the the caudate-putamen of histamine H3KO mice was lower than that in the caudate-putamen of WT mice. In contrast, there was no significant difference in the number of the psychostimulant-induced c-Fos-positive cells in the nucleus accumbens between the two strains of mice. These findings suggest that deficiency in histamine H3 receptors may have inhibitory effects on psychostimulant-induced increase in locomotion, but insignificant effects on the reward. Keywords:: histamine H3 receptor-knockout mouse, methamphetamine, 3,4-methylenedioxymethamphetamine (MDMA), sensitization of locomotion, conditioned place preference